Analysis of the Effectiveness of Interpersonal Communication Between Teachers and Parents on the Spirit of Learning Based on the Independent Curriculum (Case Study: SD Negeri Cempaka Putih Barat 01) - Supriatna, Asep; Komalawati, Euis (PT FORMOSA CENDEKIA GLOBAL, 2024)
Education is the main foundation in building an advanced and developed nation. Effective communication between teachers and parents is considered important to support students' development and learning motivation. This research uses a case study method with a qualitative approach. Data were obtained through in-depth interviews, observation and document analysis. The results show that the existence of a school committee makes open, empathetic and collaborative communication between teachers and parents have a positive impact on increasing students' enthusiasm for learning. Factors such as openness of information, trust and active participation from both parties are key to success in supporting students' enthusiasm for learning in a flexible and student-centered curriculum.